Exploring Employees’ Work-Life Harmony and Service Delivery in Mpumalanga’s Municipalities, South Africa: A Theoretical Perspective - Mkhabela, LZ.; Isabirye, AK.; Moloi, KC (Journal of Ecohumanism, 2026)
The study explores the link between employees’ work-life balance and service delivery in Mpumalanga’s municipalities, South Africa, through an extensive review of literature. Work-life harmony is vital for employee well-being as it impacts job satisfaction, motivation, efficiency, and overall organisational outcomes. Using qualitative methods, data were collected from reputable sources such as SALGA, LGSETA, and the Auditor-General, focusing on literature published over the past decade. This approach emphasised peer-reviewed articles and relevant government reports. The findings indicate that work-life balance affects employee performance and the municipality’s ability to serve communities effectively. It also shows that employees under stress find it difficult to manage work demands alongside their personal lives. We recommend that municipal leaders regularly evaluate employees’ workload and implement intervention strategies like mental health programmes, consider flexible work arrangements such as remote work, provide stress management training, establish peer support networks, and revise organisational policies that place excessive pressure on employee well-being and performance. Prioritising strategies that foster a supportive and empowering work environment is essential for reducing the risks of burnout, absenteeism, and ill health caused by workload pressures.